Sigmoid Colon Intussusception Secondary to Giant Colonic Submucosal Lipoma: A Case Report - Mohammed Alessa (Case Reports in Medicine)
Conclusion: Submucosal lipoma is a rare cause of colo-colonic intussusceptions. It should be considered in differential diagnosis.